Bicyclol attenuates high fat diet-induced non-alcoholic fatty liver disease/non-alcoholic steatohepatitis through modulating multiple pathways in mice - Jingyi Wu; Shu Jia; Benhong Xu; Xiaokun Yao; Jingping Shao; Jianzuo Yao; Danwei Cen; Xiaomin Yao (Frontiers Media S.A., 2023)
Introduction: The pathological progression of non-alcoholic fatty liver disease (NAFLD) is driven by multiple factors, and non-alcoholic steatohepatitis (NASH) represents its progressive form. In our previous studies, we found that bicyclol had beneficial effects on NAFLD/ NASH. Here we aim to investigate the underlying molecular mechanisms of the bicyclol effect on NAFLD/NASH induced by high-fat diet (HFD) feeding.Methods: A mice model of NAFLD/NASH induced by HFD-feeding for 8 weeks was used. As a pretreatment, bicyclol (200 mg/kg) was given to mice by oral gavage twice daily. Hematoxylin and eosin (H&E) stains were processed to evaluate hepatic steatosis, and hepatic fibrous hyperplasia was assessed by Masson staining. Biochemistry analyses were used to measure serum aminotransferase, serum lipids, and lipids in liver tissues. Proteomics and bioinformatics analyses were performed to identify the signaling pathways and target proteins. Data are available via Proteome X change with identifier PXD040233. The real-time RT-PCR and Western blot analyses were performed to verify the proteomics data.Results: Bicyclol had a markedly protective effect against NAFLD/NASH by suppressing the increase of serum aminotransferase, hepatic lipid accumulation and alleviating histopathological changes in liver tissues. Proteomics analyses showed that bicyclol remarkably restored major pathways related to immunological responses and metabolic processes altered by HFD feeding. Consistent with our previous results, bicyclol significantly inhibited inflammation and oxidative stress pathway related indexes (SAA1, GSTM1 and GSTA1). Furthermore, the beneficial effects of bicyclol were closely associated with the signaling pathways of bile acid metabolism (NPC1, SLCOLA4 and UGT1A1), cytochrome P450-mediated metabolism (CYP2C54, CYP3A11 and CYP3A25), biological processes such as metal ion metabolism (Ceruloplasmin and Metallothionein-1), angiogenesis (ALDH1A1) and immunological responses (IFI204 and IFIT3).Discussion: These findings suggested that bicyclol is a potential preventive agent for NAFLD/NASH by targeting multiple mechanisms in future clinical investigations.